Stromal cell-derived factor-1 (SDF-1/CXCL12) gene polymorphisms in pulmonary tuberculosis patients of south India - Selvaraj, P.; Alagarasu, K.; Singh, B. (International journal of immunogenetics, 2012)
Summary CXCL12 gene polymorphisms influence CXCL12 levels and may be associated with the outcome of host–pathogen interaction. Hence, the present study was carried out to find out whether CXCL12 gene polymorphisms are associated with susceptibility or resistance to pulmonary tuberculosis (PTB). Intron and 3′ untranslated region (UTR) polymorphisms of CXCL12 gene were investigated among 184 patients with PTB and 187 healthy controls (HC) using polymerase chain reaction‐based methods. The results revealed an increased frequency of G/A genotype of In2 +5887 [P = 0.034; odds ratio (OR) 1.66; 95% confidence intervals 1.04–2.66] and a decreased frequency of G/A genotype of 3′UTR +12197 polymorphisms (P = 0.051; OR 0.64; 95% CI 0.4–1.00) among patients than HCs. When the study subjects were categorized based on sex, significantly increased frequencies of G/A genotype (P = 0.013 Pc = 0.039; OR 2.41) of In2 +5887 and G/G genotype (P = 0.005, Pc = 0.015; OR 2.48) of 3′UTR +12197 polymorphisms were observed among female patients with PTB as compared to female HC. A significantly decreased frequency of the haplotype G‐C‐A‐T (P = 0.006, Pc = 0.030; OR 0.48) was noticed among female patients with PTB as compared to female HC. The study suggests that G/A genotype of In2 +5887 and G/G genotype of 3′UTR +12197 polymorphisms may be associated with susceptibility to PTB among females, and the haplotype G‐C‐A‐T of CXCL12 gene may be associated with protection in females.